REVIEW OF CULTURE ISSUES AND CHALLENGES AFFECTING NURSING PRACTICE IN SAUDI ARABIA - Abdulrhman Albougami; Jazi S Alotaibi, (The Malaysian Journal of Nursing (MJN), 2020)
Cultural diversity is a prominent issue in nursing practice in Saudi Arabia, which hinders the development of the profession. The presence of an expatriate nursing workforce in the region leads to issues of linguistic and cultural differences between nurses and patients. The literature reveals that conflicts between expatriate nurses and patients are caused primarily by a lack of effective communication and interaction, which, in turn, originates from differences in cultural standards. Such conflict may compromise patient care and increase the probability of medical errors. The concerned authorities must consider these issues when recruiting foreign-educated nurses. Educational and training programs must also include guidelines for cultural sensitivity so that nurses can competently deal with culturally delicate situations. Nurses must proficiently handle various aspects of cultural diversity among patients because such competencies are needed to provide effective care.